Synthesis and Characterization of Poly-Aluminum Chloride (PAC) from Aluminum Factory Waste for Water Treatment Applications - Manh Cuong, Le; Ha, Do Thi Thanh; Hoang, Le Huy; Mai, Nguyen Nhu (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 3DO - 10.25073/2588-1140/vnunst.5862, 2025)
This paper presents the results of PAC synthesis from aluminum factory waste. PAC was synthesized under the following conditions: HCl 18%, reaction temperature of 70 °C, reaction time of 15 minutes for AlCl 3 formation reaction; NaOH 6M, pH of 5, reaction temperature of 25 °C, and reaction time of 30 minutes for PAC synthesis from AlCl 3 . The synthesized PAC meets technical requirements, with an aluminum content of approximately 13%. The surface water treatment efficiency using PAC synthesized from aluminum factory waste is quite good, with turbidity notably reducing from 13NTU to 1.8NTU, meeting current Vietnam Quality Standards requirements.